2019
DOI: 10.1042/bsr20193319
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy and safety of kanglaite adjuvant therapy in the treatment of advanced hepatocellular carcinoma: A PRISMA-compliant meta-analysis

Abstract: Kanglaite, a type of Chinese medicine preparation, is considered a promising complementary therapy option for advanced hepatocellular carcinoma (HCC). Although an analysis of the published literature has been performed, the exact effects and safety are yet to be systematically investigated. Therefore, we conducted a wide-ranging online search of electronic databases to provide systematic conclusions; data from 31 trials with 2315 HCC patients were included. The results indicated that compared with conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 22 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…The main active ingredient of Kanglaite injection is a triglyceride, which contains four types of fatty acids [ 41 ]. Kanglaite injection was first approved in 1997 in China for the treatment of HCC and approved by the US Food and Drug Administration (FDA) for a phase III clinical trial in 2015 [ 42 ]. A clinical study with 156 HCC patients comparing Kanglaite injection with systemic chemotherapy showed that Kanglaite injection had similar efficacy and safety when compared to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The main active ingredient of Kanglaite injection is a triglyceride, which contains four types of fatty acids [ 41 ]. Kanglaite injection was first approved in 1997 in China for the treatment of HCC and approved by the US Food and Drug Administration (FDA) for a phase III clinical trial in 2015 [ 42 ]. A clinical study with 156 HCC patients comparing Kanglaite injection with systemic chemotherapy showed that Kanglaite injection had similar efficacy and safety when compared to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the advances in diagnostic methods, early detection of HCC remains a challenging endeavour (Liu et al. 2019 ; Anwanwan et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a considerable number of patients with liver cancer progress to the intermediate or advanced stages, and the five-year survival rate is less than 17% (Liu et al. 2019 ; Zhu et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 , 17 ] Millions cancer patients in more than 2000 hospitals in China have been treated with Kanglaite injection. [ 18 ] It has been widely used for the treatment of Pancreatic cancer, [ 19 , 20 ] lung cancer, [ 21 , 22 ] breast cancer, [ 23 ] colorectal cancer, [ 24 ] hepatocellular carcinoma, [ 25 ] and GC. [ 26 , 27 ] Researches showed that Kanglaite injection could effectively reverse multiple-drug resistance in cancer cells and enhance the sensitivity of tumor cells to chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%